Elements of Corporate Governance in Tourism Organizations - Pechlaner, Harald; Raich, F.; Kofink, L. (University of the Aegean, Chios, 2011)
Tourism organizations used to be central players when it came to destination management. However, demands from the market — but also from local stakeholders — have changed significantly, both in form and content. One approach to further develop and professionalize tourism organizations is to apply the concept of corporate governance. It offers organizations a set of instruments to govern, control and monitor themselves, and enables the implementation of previously defined structures and standards. This article analyzes whether selected elements of corporate governance are applied in tourism organizations in the Alps, and what characteristics these elements offer. Our results show that tourism organizations are aware of the selected corporate governance elements, and even of their potential, but the degree and extent of their application so far has been rather poor.